Development and characterization of linseed-mustard and castor-mustard oil coated DAP formulations - Prem, Kumar B; Biswas, D R; Sharma, V K; Basak, B B; Bhattacharyya, R; Das, S; Dass, A; Bhatia, A; Rupesh, T; Sarkar, A; et al. (Plant Science Today, 2026)
Oil based coatings provide a biodegradable and low-cost strategy for developing Controlled-Release Fertilizers (CRFs). In this study, 18 oil-coated phosphorus (P) fertilizer formulations were prepared using diammonium phosphate (DAP) as core nutrients and linseed, castor and mustard oils in defined blend ratios (100:0, 75:25, 50:50) at three coating levels (5 %, 10 %, 15 %). Curing behavior was assessed for 45 days, followed by characterization using Fourier Transform Infrared (FTIR) spectroscopy and Scanning Electron Microscopy (SEM). Phosphorus release kinetics were evaluated in an aqueous medium over 30 days and fitted to both first-order and Korsmeyer-Peppas (KP) models. Curing data indicated that 100 % linseed oil underwent the highest oxidation-driven weight gain (≈5 % by day 10) followed by shrinkage, whereas 50:50 oil blends showed minimal weight fluctuations (< 1 % by day 10) and stable film formation. FTIR confirmed oxidation and polymerization (C-O-C, C=O, C=C) with preservation of phosphate bands. SEM revealed smooth, continuous coatings for linseed oil-mustard oil (LM) formulations and thicker, more flexible films for castor oil-mustard oil (CM) formulation. Release studies showed significantly reduced dissolution from all coated fertilizers (60–70 % in case of LM coated DAP and 60–80 % in case of CM coated DAP) compared to uncoated DAP ( 94 % release) at 30 days. Kinetic modeling demonstrated that most LM-coated DAP formulations followed Korsmeyer-Peppas (non-Fickian) behavior, whereas several CM formulations followed first-order kinetics. Overall, LM blends at 75:25 and 50:50 with a 10 % coating level exhibited optimal curing stability and controlled-release behavior, marking them promising formulations for subsequent soil incubation and greenhouse evaluation.